Ação de fungicidas no desenvolvimento de plantas de tomate, em condições de ambiente protegido - Jacobelis Junior, Walter [UNESP] (2015)
This experiment has the purpose to study the physiological effects of strobilurine and carboxamides in metabolism and development of plants, as increased production and fruit quality of hybrid Conquistador tomato (Solanum lycopersicum L.) in greenhouse conditions. This experiment was conduct in an experimental field of the School of Agronomical Sciences at the Universidade Estadual Paulista, Botucatu-SP Campus. The experimental design consisted in randomized blocks in tomato plants with 5 fungicide treatments: control, azoxystrobin (75 g ha-1), boscalid (75g ha-1), pyraclostrobin (75 g ha-1), fluxapyroxad (75g ha-1) and the formulation with fluxapyroxad (50g ha-1) + pyraclostrobin (100 g ha-1), 6 applications with 7 days intervals, the first being 3 days after transplantation. The effect of the treatments were evaluated through observation of the following characteristics: production of fruits and fruit weight, gas exchange, chlorophyll content in leaves and activity of peroxidase, superoxide dismutase, catalase and nitrate reductase. According to the obtain results, it is conclude that the fungicides have positive physiological effects on tomato plants grown in greenhouse conditions, which increased fruit production, the activity of the enzyme nitrate reductase, and the activity of the antioxidant system and chlorophyll index, and these effects were more evident in plants treated with pyraclostrobin, boscalida and fluxapyroxad.